Mechanically adaptive hydrogels for bone tissue engineering: from classification and biomechanics to modeling and translational applications - Băncilă, Ioana-Cristina (Frontiers in Medical Engineering, 2025)
Hydrogels are key materials in bone tissue engineering due to their high water content, biocompatibility, and tunable mechanics. Mechanically adaptive hydrogels, a class of smart biomaterials, can dynamically adjust stiffness and viscoelasticity in response to environmental cues, closely mimicking bone extracellular matrix behavior. This review critically synthesizes the hydrogel types, biomechanical properties, and scaffold fabrication strategies, with a focus on mechanically responsive systems. Finite element modeling (FEM) is highlighted as a predictive tool for scaffold design, while bone-on-chip (BoC) platforms provide physiologically relevant in vitro evaluation. Recent advances in composite hydrogels, reinforcement methods, and multi-scale modeling are analysed to identify gaps in standardization, mechanical mapping and biological outcomes. By linking mechanical adaptability to clinical scenarios such as craniofacial reconstruction, spinal fusion, and osteochondral repair, this review provides a concise framework for the rational design and translation and future research in mechanically adaptive hydrogels in bone regeneration.